Clinicopathologic Characteristics and Survival of Patients With Bone Metastasis in Yazd, Iran: A Cross-Sectional Retrospective Study - Shabani, Masood (Medicine (Baltimore), 2014)
To evaluate the clinico-pathological and survival characteristics in patients with bone metastasis. This cross-sectional study was conducted on patients with bone metastasis who referred to Shahid Ramezanzadeh radiation oncology center. For all of the patients studied, demographic and survival information was recorded. SPSS was used to analyze the data. In this study, 89 men (53.3%) and 78 women (46.7%) with bone metastasis were examined. Most of the patients were in the 66 to 87 age range. Breast cancer was the most common type of cancer in women and prostate cancer was the commonest in men. In most patients, pain was the first manifestation of the disease, and the spine has been most frequently involved areas. The disease was diagnosed by isotope bone scan in the most cases. The mean survival was 31.1 months for patients with breast cancer, 12.9 months for patients with prostate cancer, 13.7 months for patients with lung cancer and the overall survival was 22.5. There was only a meaningful correlation between sex, type of cancer, radiation dose, and survival in patients. We found that age was more effective than the variable of cancer type in survival of patients with bone metastasis. The prognosis of patients with bone metastasis in our center is fair. There was a significant correlation between sex, type of cancer, radiation dose, and survival. Cox proportional hazards model showed that age was a predictor of death.